Katie and the Mustang. Book four - Duey, Kathleen (New York, N.Y., U.S.A. : Puffin Books, 2004)
Katie continues the journey west to Oregon hoping to be reunited with her uncle and returning the Mustang closer to his homeland.
008-012.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Orphans -- Fiction; Horses -- Fiction; Wild horses -- Fiction; Frontier and pioneer life -- Fiction